(untitled) (Communication & Society, 2020)
This paper investigates the evolution of non-daily current affairs formats –other than the news– in the prime time of Spanish generalist television between 1990 and 2016. Analysing the programming content of six channels (TVE, La2, Antena 3, Telecinco, Cuatro and La Sexta), we have studied the presence, typology and strategies of the programmers to incorporate them into the offer of prime time. The longitudinal sample allows us to detect the tendencies that have influenced the audiovisual treatment of the non-daily current affairs information in the most competitive television time slot. The result of the analysis shows that the most important topics on current affairs such as politics, or the economy, have been integrated into the prime time. In addition, there has been a recovery of analytical genres such as the television reportage to explain topics of current interest. This new informative offer, much more innovative in the treatment, has enabled new programming strategies to be applied to the non-daily current affairs formats in order to improve their profitability.